2020
DOI: 10.3389/fnins.2020.00141
|View full text |Cite
|
Sign up to set email alerts
|

ALFF and ReHo Mapping Reveals Different Functional Patterns in Early- and Late-Onset Parkinson’s Disease

Abstract: Heterogeneity between late-onset Parkinson's disease (LOPD) and early-onset Parkinson's disease (EOPD) is mainly reflected in the following aspects including genetics, disease progression, drug response, clinical manifestation, and neuropathological change. Although many studies have investigated these differences in relation to clinical significance, the functional processing circuits and underlying neural mechanisms have not been entirely understood. In this study, regional homogeneity (ReHo) and amplitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 70 publications
1
28
0
Order By: Relevance
“…The patients with EOPD and LOPD had different patterns of alterations in emotion and cognition-related circuits compared with their age-matched healthy control in the previous studies (32,33). In EOPD, decreased cerebral regional homogeneity (ReHo) values were found in parts of the frontal and left temporal regions (32). In LOPD, increased ReHo values were found in the left angular gyrus (32).…”
Section: Discussionmentioning
confidence: 88%
“…The patients with EOPD and LOPD had different patterns of alterations in emotion and cognition-related circuits compared with their age-matched healthy control in the previous studies (32,33). In EOPD, decreased cerebral regional homogeneity (ReHo) values were found in parts of the frontal and left temporal regions (32). In LOPD, increased ReHo values were found in the left angular gyrus (32).…”
Section: Discussionmentioning
confidence: 88%
“…In the last 5 years, blood oxygenation level-dependent resting-state functional magnetic resonance imaging (rs-fMRI) has become a commonly used research instrument for exploring changes in spontaneous brain activity in PD (Fox and Raichle, 2007 ; Van Eimeren et al, 2009 ). Functional neuroimaging studies of EOPD and LOPD have mostly focused on spontaneous brain activity as measured by regional homogeneity (ReHo; Sheng et al, 2016 ; Yue et al, 2020 ), the amplitude of low-frequency fluctuation (ALFF; Yue et al, 2020 ), and functional connectivity (FC; Hou et al, 2016 ). However, there are many inconsistencies in the findings, and it remains unclear which neuroimaging markers are more reliable for evaluating the pathophysiologic and clinical differences between EOPD and LOPD.…”
Section: Introductionmentioning
confidence: 99%
“…Yue et al used amplitude of low-frequency fluctuation (ALFF) to analyze the differences in brain activity before and after DBS surgery found that the ALFF value of the precentral gyrus decreased after surgery. ReHo revealed the neural synchronization of local brain regions activity, while ALFF reflected the spontaneous neural activity of local brain regions [ 16 ]. ALFF combined with the ReHo method can reflect the pattern of neural activity more comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…e ReHo method indirectly reflects the spontaneous activity of neurons by analyzing the consistency of signaling fluctuations in the spatial adjacent voxel oxygen levels simultaneously using Kendall's coefficient of concordance (KCC) [14]. Reho has been widely used to study abnormalities in brain activity in PD [15][16][17] and can even be used as a potential imaging marker for PD [15,18]. Conducting the ReHo method of the entire gray mass of the brain has almost shown test-retest reproducibility [19].…”
Section: Introductionmentioning
confidence: 99%